PEMBERDAYAAN MASYARAKAT DESA BANJAROYO, KALIBAWANG, KULON PROGO DALAM BIDANG KESEHATAN - Rustiawan, Asep; Ruminda, Afdilla Puja; Adriansyah, Bobby; Prasetya, Virdinan Dharma (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
The community of Banjaroyo, Kalibawang - Kulon Progo Yogyakarta has poor clean and healthy lifestyle habits (CHLH) which still do not like washing hands with soap and unhealthy snacks. Besides that, knowledge of dengue disease is also still low with the condition of dengue endemic areas. The 71st period of the UAD Community Service Program conducted from 23 January to 20 February 2019 was intended to empower the community through the dissemination of CHLH and DHF. The method used consisted of lectures, demonstrations and special practices for Hand Washing with Soap, while for Snacks and DHF the lecture method was used. The impact of these program are the increased knowledge and skills of the community in the field of CHLH, especially how to wash hands properly using soap, choose healthy snacks and efforts to prevent dengue disease.